Reconsidering Capacity to Appoint a Healthcare Proxy - Appel, Jacob M. (Cambridge quarterly of healthcare ethics, 2023)
Clinicians are often called upon to assess the capacity of a patient to appoint a healthcare agent. Although a consensus has emerged that the standard for such assessment should differ from that for capacity to render specific healthcare decisions, exactly what standard should be employed remains unsettled and differs by jurisdiction. The current models in use draw heavily upon analogous methods used in clinical assessment, such as the "four skills" approach. This essay proposes an alternative model that relies upon categorization and sliding scale risk assessment that can be used to determine to how much scrutiny the proxy appointment should be subjected and how much certainty of accuracy should be required in order to maximize the patient’s autonomy and ensure that her underlying wishes are met.